Is there Learning Continuity during the COVID-19 Pandemic? A Synthesis of the Emerging Evidence - McBurnie, Chris; Adam, Taskeen; Kaye, Tom (Journal of Learning for Development, 2020)
Since the onset of COVID-19, governments have launched technology-supported education interventions to ensure children learn. This paper offers a narrative synthesis of emerging evidence on technology-based education to understand the current experiences of learners, teachers and families. Studies find that few students in low- and middle-income countries have access to technology-supported learning with the most marginalised children appearing to have the least educational opportunities. As such, the education response to COVID-19 could widen existing inequalities.
Keywords: dode_eth-src-dode; dode_eth-trf2-dode; ⛔ No DOI found

The relationship between educational television and mathematics capability in Tanzania - Watson, Joseph; Hennessy, Sara; Vignoles, Anna (British Journal of Educational Technology, 2020)
Previous studies have frequently demonstrated that educational television viewing can have a positive effect on learning in low-income country contexts when shows are delivered in controlled settings. However, the consequence of day-to-day viewing in such contexts has scarcely been considered. Additionally, no recent published research has provided any information on the costs of educational television. The lack of research in these areas is striking. Examining educational television viewing in monitored settings provides limited information on the influence of routine television consumption. Further, the broad reach of numerous educational television programmes should provide low perviewer costs and, resultantly, strong cost-effectiveness findings. This PhD study therefore examined (1) the association between educational television exposure and mathematics capability and (2) the cost effectiveness of educational television interventions. To achieve this, research was carried out that centred on Ubongo Kids – a popular Tanzanian-produced show delivering mathematics-focused content.
Keywords: Tanzania; ___working_potential_duplicate; cost effectiveness; educational television; mathematics; ⛔ No DOI found